2016
DOI: 10.1002/mabi.201600174
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Crosslinking of Polymer Conjugates is Superior over Ionic or UV Crosslinking for the On‐Chip Production of Cell‐Laden Microgels

Abstract: Cell-laden micrometer-sized hydrogels (microgels) hold great promise for improving high throughput ex-vivo drug screening and engineering biomimetic tissues. Microfluidics is a powerful tool to produce microgels. However, only a limited amount of biomaterials have been reported to be compatible with on-chip microgel formation. Moreover, these biomaterials are often associated with mechanical instability, cytotoxicity, and cellular senescence. To resolve this challenge, dextran-tyramine has been explored as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Microfluidic platforms have been used to microfabricate hydrogel spheres with well-defined diameters, architectures, and chemical compositions [6064], as well as fibers of a particular architecture including hollow fibers and gradients within hydrogels [65]. Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64]. Recent innovations even allowed for microfluidic encapsulation of individual cells in microgels that are only marginally larger than the cell they contain [66].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…Microfluidic platforms have been used to microfabricate hydrogel spheres with well-defined diameters, architectures, and chemical compositions [6064], as well as fibers of a particular architecture including hollow fibers and gradients within hydrogels [65]. Numerous studies have demonstrated the generation of cell-laden hydrogel microparticles using microfluidic devices[64]. Recent innovations even allowed for microfluidic encapsulation of individual cells in microgels that are only marginally larger than the cell they contain [66].…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%
“…remaining PDMS particles from inlet punching) from interfering with the droplet generation or crosslinking processes (Figure 4d). Furthermore, the aqueous phase inlet contained a previously reported pillar structure 13 that ensured particle homogenization to aid evenly distributed encapsulation of particles (e.g. cells) (Figure 4e).…”
Section: -37mentioning
confidence: 99%
“…[8][9][10] In particular, emulsions can be continuously produced at high rates while stabilizing surfactants make them compatible with relatively slow (seconds to minutes) gelation mechanisms such as Michael-type addition, 11 temperature-dependent gelation, 12 and enzyme-based crosslinking approaches. 13 The majority of polymer gelation strategies however requires the presence of crosslinker molecules such as ions and radicals, 14 which is not trivial in emulsions, as these are typically multiphase immiscible systems where oil hampers the direct mixing of the hydrogel precursor and its crosslinker.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations